The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis. (18th August 2020) - Albrecht, Matthias; Kleijn, David; Williams, Neal M.; Tschumi, Matthias; Blaauw, Brett R.; Bommarco, Riccardo; Campbell, Alistair J.; Dainese, Matteo; Drummond, Francis A.; Entling, Martin H.; Ganser, Dominik; Arjen de Groot, G.; et al.
Abstract: Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future. Abstract : Our quantitative synthesis of the impacts of floral plantings on pest control, crop pollination and yield reveals that flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average, while effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of this variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively, with important implications for the the design and implementation of these measures to effectively promote ecological intensification of agriculture in the future